Traditional and commercial alcohols and esophageal cancer risk in Kenya. Issue 3 (12th November 2018) - Menya, Diana; Kigen, Nicholas; Oduor, Margaret; Maina, Stephen Karuru; Some, Fatma; Chumba, David; Ayuo, Paul; Osano, Odipo; Middleton, Daniel RS; Schüz, Joachim; McCormack, Valerie A
Abstract : Squamous cell esophageal cancer is common throughout East Africa, but its etiology is poorly understood. We investigated the contribution of alcohol consumption to esophageal cancer in Kenya, based on a hospital‐based case–control study conducted from 08/2013 to 03/2018 in Eldoret, western Kenya. Cases had an endoscopy‐confirmed esophageal tumor whose histology did not rule out squamous cell carcinoma. Age and gender frequency‐matched controls were recruited from hospital visitors/patients without digestive diseases. Logistic regression was used to calculate odds ratios (ORs) and their 95% confidence intervals (CI) adjusting for tobacco (type, intensity) and 6 other potential confounders. A total of 422 cases (65% male, mean at diagnosis 60 (SD 14) years) and 414 controls were included. ORs for ever‐drinking were stronger in ever‐tobacco users (9.0, 95% CI: 3.4, 23.8, with few tobacco users who were never drinkers) than in never‐tobacco users (2.6, 95% CI: 1.6, 4.1). Risk increased linearly with number of drinks: OR for >6 compared to >0 to ≤2 drinks/day were 5.2 (2.4, 11.4) in ever‐tobacco users and 2.1 (0.7, 4.4) in never‐tobacco users. Although most ethanol came from low ethanol alcohols ( busaa or beer), for the same ethanol intake, if a greater proportion came from the moonshine chang'aa, it was associated with a specific additional risk. The population attributable fraction for >2 drinks per day was 48% overall and highest in male tobacco users. Alcohol consumption, particularly of busaa and chang'aa, contributes to half of the esophageal cancer burden in western Kenya. Abstract : What's new? The authors investigated the role of commercial and locally manufactured alcohols in esophageal cancer in Kenya, a common cancer in East Africa. Alcohol was a large contributor to the cancer burden, particularly in men. Most ethanol came from the traditional brew busaa ; and a particularly strong increased esophageal cancer risk was seen for the traditional spirit chang'aa . Alcohol consumption needs to be reduced in Kenya to prevent this common fatal cancer.